Strategic Framework for Reconstruction in Syria: Theoretical foundations, national approach and policy integration (Damascus University Journal for the economic and Political sciences, 2021)
Syria is going through an exceptional war that requires new approaches that are comprehensive, gradual and participatory in order to deal with the effects of the crisis-war.This research employs the approach of the overall political economy to provide a policy approach within a strategic framework that stems from the cultural heritage and the future vision in the reconstruction phase in Syria.Where the intellectual foundations are integrated into national programs that represent the basis for gradualization in the event of stability and comprehensive and sustainable recovery and based on two assumptions:First, economic growth does not necessarily lead to comprehensive development in the reconstruction phase. All strategies must be developed in their local context, with multiple strategies being integrated at the same time according to the contexts and within the spatial development and urbanization perspectives.Second: The centrality of the role of the state-citizen in promoting the process of comprehensive and sustainable development, avoiding ambiguous practices and random paths, and the sense of slow process of construction as a result of urgent needs, so that Syria is more than ever a place for all. .The research aims at presenting a holistic approach to reconstruction from the point of view of the political economy (after diagnosing the course of past development and the effects of the crisis-war) within a strategic framework stemming from the cultural heritage and the future vision of Syria.
Keywords: reconstruction; political economy; economic growth; economic development; economic policies; strategic planning